Efficient diffusion of renewable energies: A roller-coaster ride - Carsten Helm; Mathias Mier (University of Oldenburg, Department of Economics, 2016)
When the supply of intermittent renewable energies like wind and solar is high, the electricity price is low. Conversely, prices are high when their supply is low. This reduces the pro t potential in renewable energies and, therefore, incentives to invest in renewable capacities. Nevertheless, we show that perfect competition and dynamic pricing lead to efficient choices of renewable and fossil capacities, provided that external costs of fossils are internalized by an appropriate tax. We also investigate some properties of electricity markets with intermittent renewables and examine the market diffusion of renewables as their capacity costs fall. We show that the intermittency of renewables causes an S-shaped diffusion pattern, implying that a rapid build-up of capacities is followed by a stage of substantially slower development. While this pattern is well known from the innovation literature, the mechanism is new. Moreover, the S-shaped pattern is followed by another acceleration phase towards the end of the diffusion process. We also find that technology improvements such as better storage capabilities have substantial effects not only on the speed of market penetration, but also on its pattern. Finally, fluctuations of energy prices rise with the share of renewables. If regulators respond with a price cap, this leads to a faster market diffusion of renewables.
Keywords: 330; renewable energies; peak-load pricing; intermittent energy sources; technology diffusion; price caps; energy transition